Impact of Fusarium head blight and mycotoxins prodced by Fusarium avenaceum on quality and safety of malting barley - INBAIA, SAFIEDDIN (2021)
Fusarium head blight (FHB) is a devastating fungal disease of barley and other small-grain cereals worldwide, caused by a complex of toxigenic Fusarium spp. and non-toxigenic Microdochium spp. This disease causes detrimental yield losses, reduces grain quality and leads to mycotoxin contamination of grain. Fusarium avenaceum, which is frequently isolated from small-grain cereals, causes FHB disease in the cooler climes of Northern and Central Europe. This is a species associated with significant production of enniatin (ENN A, A1, B and B1), moniliformin (MON), and occasionally, beauvericin (BEA) mycotoxins. Although no maximum levels of ENNs, BEA and MON have been legislated for until now, their toxic effects in combination with high contamination levels in food suggest that they may pose hazards to human health. The aim of this study was to determine whether UK isolates of F. avenaceum cause Fusarium seedling blight (FSB), Fusarium foot rot (FFR) and FHB in UK barley, and if so, how aggressively. A further aim was to ascertain the mycotoxin range and impact on quality and safety during the milling and malting processing of barley grain. New separation conditions of liquid chromatography with tandem mass spectrometry (LC-MS/MS) were developed to detect and quantify BEA, ENNs and MON in barley grain. The limit of detection (LOD) and limit of quantification (LOQ) for the mycotoxins ranged from 0.1-0.9 µg kg-1 for ENN A and MON and 2.0-4.0 µg kg-1 for ENN B1 and MON, respectively, with a relative standard deviation (RSD) of less than 10%. The most common mycotoxins found in 223 survey samples from commercially grown UK malting barley collected between 2007 and 2011 were ENN B, B1 and A1, in that order; however, BEA and ENN A were not detected. ENN B had the highest incidence of 100% in 2007 and the lowest incidence of 68.5% in 2011, with mean concentrations of 3072.9 and 1977.9 µg kg-1, respectively. MON was quantified only in samples from 2010 and 2011, with incidence rates of 10.1% and 15.5% and concentrations of 5.1-45.3 µg kg-1. There were five regions within the UK, South, East, Midlands and North of England and Scotland. Year and region had a significant interaction on ENN A1 and B1, but there was no significant interaction in ENN B. The incidence of ENN A1, B and B1 were higher average concentrations in East of England compared with other regions in the UK. In vivo and in vitro experiments were conducted as a series to determine the aggressiveness and mycotoxin profiles of UK isolates of F. avenaceum. The study used artificial inoculation with nine isolates of F. avenaceum on the barley varieties Moonshine and Quench. There was significant variation between F. avenaceum isolates in their ability to cause FSB and FHB diseases and mycotoxin production. Fa225, Fa40, Fa219 and Fa75 were found to be more aggressive in causing FSB and FHB diseases and more toxigenic because these isolates produced ENN A1, B and B1 under both in vitro and in vivo experimental conditions. Fa235 and Fa55 proved to be moderately aggressive, whereas Fa248, Fa210 and Fa74 produced the lowest FSB and FHB symptoms and the lowest levels of ENN A1, B and B1 concentrations in in vitro experiments, and they only produced ENN B and B1 under in vivo experimental conditions. ENN B had the greatest concentrations in inoculated barley heads, ranging from 690 to 7510 µg kg-1 in vivo, followed by ENN B1 and A1; however, BEA and ENN A were not detected, and not all isolates produced ENN A1. It is worth noting that the level of ENN B was significantly higher in vitro, ranging from 2030 to 81850 µg kg-1, followed by ENN B1 and A1; however, BEA and ENN A were not detected. The barley cv. Moonshine was more resistant and accumulated fewer mycotoxins than cv. Quench did. MON was not quantified in in vivo experiments; however, all isolates of F. avenaceum produced MON under in vitro experimental conditions. A field experiment was conducted to determine the severity of FHB caused by individual F. avenaceum isolates, the fate of mycotoxins during the milling and malting barley processes and the impact of individual isolates on the quality of malting barley. Disease assessments revealed a significant variation between the isolates of F. avenaceum in causing FR and FHB diseases. Isolates of F. avenaceum Fa40, Fa225, Fa219 and Fa75 showed more severe FR and FHB disease and were capable of producing ENNs A1, B and B1, but BEA and ENN A were not detected. Fa235 and Fa55 were moderately aggressive, whereas Fa248, Fa210 and Fa74 produced the lowest FR and FHB symptoms and the lowest levels of ENN B and B1 concentrations under field conditions. ENN A1, B and B1 ranged from 63.6 to 148.9, 20.5 to 245.8 and 63.6 to 148.9 µg kg-1, respectively, and the barley cv. Concerto was more resistant than cv. Propino, accumulating fewer mycotoxins. A significant positive relationship was found between the total amount of F. avenaceum DNA and the quantified mycotoxins. The yield quality, specific weight (SPW), thousand-grain weight (TGW) and germinative energy of barley were significantly reduced following inoculation with F. avenaceum isolates. Three inoculated samples by isolates of F. avenaceum were chosen to investigate the fate of ENNs during milling, bread making and malting barley processing. Analysis of the pilot mill fractions identified a significant difference between the proportions of ENN A1, B and B1 and between varieties. ENN A1, B and B1 were higher in bran fractions and lower in flour, which slightly higher in the barley cultivar cv. Propino. The final baking at 237 °C for 15 minutes resulted in a further decrease in ENN B, B1 and A1, ranging from 13.9% to 41.2% of their initial levels in the barley flour used as raw material. During malting barley processing, steeping removed 4.0%-37.0% of ENNs B, B1 and A1; however, ENNs were significantly increased during the period of germination. At the kilning stage, approximately 33.8%-77.7% of ENNs B, B1 and A1 were reduced after the rootlets were discarded. The barley cv. Concerto and cv. Propino were micro-malted and subjected to malt and wort analysis of quality parameters. Infection of barley grain by F. avenaceum can be correlated with increased friability and wort colour, lower amylase activity, a greater proportion of FAN and decreased wort viscosity. Thus, the quality of malt production, which is used in the brewing industry, could be reduced. Current research findings suggest that UK isolates of F. avenaceum are significant seedling blight, FR and FHB disease-causing fungi of commercial UK barley varieties and are capable of reducing yield and malt quality. Hence, research efforts should be pursued to provide tools to improve strategies aimed at controlling the infection of F. avenaceum, subsequently reducing levels of this class of mycotoxins in barley grain and their products.